Insurgent capitalism: Island, bricolage and the re-making of finance - MacKenzie, Donald; Pablo Pardo-Guerra, Juan (Economy and society, 2014)
Drawing on recent discussions of the material cultures of markets and of financial innovation as bricolage, this paper explores the development of Island, a new share-trading venue set up in 1995. We examine Island's roots in a very specific conflict in the US financial markets and in the information libertarianism of 'hacker culture', and examine the material bricolage involved in Island's construction. The paper also outlines the processes that led to a dramatic 'Latourian' change of scale: Island was originally a 'micro' development on the fringes of US markets, but within little more than a decade key features of Island became close to compulsory, as the nature of North American and Western European share trading changed utterly.